Curcumin nanofibers for the purpose of wound healing. Issue 5 (28th October 2018) - Fereydouni, Narges; Darroudi, Majid; Movaffagh, Jebrail; Shahroodi, Azadeh; Butler, Alexandra E.; Ganjali, Shiva; Sahebkar, Amirhossein
Abstract: Poor wound healing is a highly prevalent clinical problem with, as yet, no entirely satisfactory solution. A new technique, termed electrospinning, may provide a solution to improve wound healing. Due to their large surface area to volume ratio and porosity, the nanofibers created by electrospinning are able to deliver sustained drug release and oxygen to the wound. Using different types of polymers with varying properties helps strengthening nanofiber and exudates absorption. The nanofibers appear to have an ideal structure applicable for wound healing and, in combination with curcumin, can blend the anti‐inflammatory and antioxidant properties of curcumin into a highly effective wound dressing. The use of suitable curcumin solvents and the slow release of curcumin from the nanofiber help in overcoming the known limitations of curcumin, specifically its low stability and limited bioavailability. Here, we review the studies which have been done on synthesized nanofibers containing curcumin, produced by the electrospinning technique, for the purpose of wound healing. Abstract : Curcumin is a phytochemical with diverse biological properties that could contribute to accelerated wound healing. Formulation of curcumin into nanofibers created using electrospinning process has been suggested as a promising strategy to improve the delivery of curcumin to wound tissue. Here, we review the extant evidence on the use of synthesized curcumin nanofibers for the purpose of wound healing.